Seasonality of Post-capture Longevity in a Medically-Important Mosquito (Culex pipiens) - Papadopoulos, Nikos T.; Carey, James R.; Ioannou, Charalampos S.; Ji, Hao; Müller, Hans-Georg; Wang, Jane-Ling; Luckhart, Shirley; Lewis, Edwin E. (Frontiers in Ecology and Evolution, 2016)
The epidemiological importance of the age structure and longevity potential of wild populations of mosquito disease vectors has been known for over 60 years. However, no routine method currently exists that provides reliable insights into the population age dynamics of this medically-important group of insects. In this paper we use a technique originally developed for studying wild fruit fly populations to study the post-capture longevity dynamics in populations of the West Nile virus mosquito Culex pipiens in Greece. This approach, referred to as the captive cohort method, analyzes and interprets the longevity trends in wild-caught Cx. pipiens to infer demographic changes in their field population. Approximately 10 adult females were captured each day from June through November, housed in individual cages in the laboratory, and their remaining longevity recorded. Strong differences were observed in the mean, variation, and extremes of post-capture longevity. Early season (June-July) mosquitoes lived the shortest and late-season the longest with a clear transition period in September. The mean levels of post-capture longevity were quite high at over two months in early season to over 85 days in late season when the vast majority of adults were nulliparous and likely preparing for hibernation. Implications for both basic and epidemiological research on the biodemography of aging in the wild are discussed.